Synthesis of Al-incorporated sulfated zirconia with improved and stabilized surface sulfur species for removal of trace olefins from aromatics. Issue 1 (18th November 2021) - Wang, Sitan; Yin, Tao; Meng, Xuan; Liu, Naiwang; Shi, Li
Abstract : Incorporating Al into zirconia significantly improves and stabilizes the surface sulfur species. The outstanding catalytic performance of Al-incorporated sulfated zirconia was obtained when it was applied in removing trace olefins from aromatics. Abstract : Al-Incorporated sulfated zirconia with improved and stabilized surface sulfur species was synthesized via the co-precipitation method and used as an effective catalyst to remove trace olefins from aromatics in a fixed-bed reactor. The textural and chemical properties of various catalysts were characterized by XRD, 27 Al MAS NMR, N2 adsorption, EA, XPS, H2 -TPR, FT-IR, and pyridine-infrared (IR) spectroscopy techniques to elucidate the Al promoting effect on acid centres and catalytic performance. The results demonstrated that incorporating Al into zirconia could effectively stabilize the tetragonal zirconia with small grain size and improve surface sulfur species, thereby balancing the distribution of Brønsted and Lewis acid sites. Consequently, sulfated zirconia incorporating Al at the level of Al/Zr < 7.5 mol% exhibited more outstanding catalytic activity and stability under a long reaction time compared with conventional sulfated zirconia. Notably, superior reusability with a negligible drop in olefins conversion over five reaction cycles was obtained in the presence of the Al2.50 -SZ. The alkylation reaction process of olefins with aromatics was further investigated by the GC-MS technique when Al x -SZ was used as the catalyst.